PENERAPAN METODE LANGSUNG DALAM MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS SISWA - Arum Putri Rahayu (Jurnal Paradigma, 2022)
This study aims to find out the factors that affect the English-speaking ability of students. In addition, it is also to know the application of direct methods in improving their speaking ability. The results of the study showed that the use of direct methods can improve the English speaking skills of students at the beginner level in the English Center course institute. This can be seen from the results achieved by students at the time of being given the test. The average score of students on the initial test was 30.6% which is categorized as still very lacking. After being given treatment in Cycle I, the average score of students increased to 47.7% and was still in the less category. However, in cycle II the average score of students increased to 71.3% and was in a good category. Students are able to speak in the context of a simple conversation. They are able to use certain phrases and vocabulary effectively.